Gambaran PHBS di Institusi Pendidikan Wilayah Kerja Puskesmas Jagir Surabaya - Adella Eka Savitri; Budhi Setianto; Aviana Gita Lara (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Efforts to improve the quality of human resources through education and health must of course start early, both during preschool and school years. The implementation of PHBS in schools needs to be instilled by the school community so that all students become accustomed to implementing it. The purpose of this study was to find out the description of PHBS in educational institutions within the working area of ​​the Jagir Health Center. This study used a descriptive quantitative study with a cross-sectional approach and data collection was carried out by observation and a checklist of educational institution PHBS assessment questionnaires. There are 18% of elementary schools in class III, and 82% in class IV. There are 11% of junior high schools that are included in classification III, and 89% are included in classification IV. There are 100% of high school schools that fall into the classification of classification IV. The intervention provided by the Jagir Health Center was conducting counseling for UKS teachers. In addition, the Jagir Health Center also carried out other intervention programs, namely measuring PHBS in every educational institution twice a year. Support and introduction of the PHBS program for school principals, teachers, school caretakers, canteen keepers by holding regular meetings in the context of forming healthy schools.